PENGARUH IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN LEVEL PELAKSANA DI DIVISI OPERASI PT. PUSRI PALEMBANG - Kiki Cahaya Setiawan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This study aims to determine influence of organizational climate on the performance of operational-level employees in the Operations Division of PT. Pusri Palembang. Operational-level employees in doing their jobs, will interact with various conditions of working environment. Working environment in the Operations Division PT. Pusri Palembang will be perceived by employees in operational-level as organizational climate.With sampling technique of proportional random sampling and using path analysis to analyse the data. The sample of this research covers 250 operational-level employees.Conclude that there was significant influence on the performance of organizational climate of operational-level employees in the operations division of PT. Pusri Palembang. Based on the findings in this study, it is necessary to create a pleasant organizational climate for Operational-level employees.if this dimension can be created in companies that can maintain and improve the performance of operational -level employees.